Prevalence and Safety of Left-Footed Driving in Right Foot Surgery Patients: A Retrospective Survey and Driving Simulation Study. Issue 4 (16th October 2019) - McKissack, Haley M.; Chodaba, Yvonne E.; Bell, Tyler R.; Lehtonen, Eva J.; Araoye, Ibukunoluwa B.; Shah, Ashish B.; Stavrinos, Despina; Johnson, Michael D.
Category: Post-operative Driving Introduction/Purpose: For many patients, returning to driving after right foot and ankle surgery is a concern, and it is not uncommon for patients to ask if driving may be performed with their left foot. A paucity of literature exists to guide physician recommendations for return to driving. The purpose of this study is to describe the driving habits of patients after right-sided foot surgery and assess the safety of left foot driving using a driving simulator. Methods: Patients who underwent right foot or ankle operations between January 2015 and December 2015 were retrospectively identified. A survey assessing driving habits prior to surgery and during the recovery period was administered via REDCap database through email or telephone. Additionally, simulated driving scenarios were conducted using a driving simulator in 20 patients to compare characteristics of left versus right foot driving. Results: Thirty six of 96 (37%) patients who responded to the survey reported driving with the left foot postoperatively. No trends were found associating left foot driving prevalence and socioeconomic status. In driving simulations, patients exceeded the speed limit significantly more (p<0.001) and hit other vehicles more (p<0.026) when driving with the right foot than the left. Time to fully brake and fully release the throttle in response to vehicular hazards were significantly prolonged in left foot driving compared to right (p = 0.019 and p = 0.034, respectively). Conclusion: A significant proportion of right foot and ankle surgery patients engaged in left foot driving during postoperative recovery. Driving with the left foot may prolong brake and throttle release times, and is therefore not recommended.